Penurunan Kadar Air untuk Memperpanjang Daya Awet Produk Wadi Ikan Patin (Pangasius hypophthalmus) - Restu Restu (Fakultas Peternakan Universitas Kristen Palangka Raya, 2015)
This study aims to determine the water content which ideal for wadi products with low salt content, so it can be stored at room temperature (28-30ºC) in a longer time. The results showed that the lower of water content, the product can be stored longer time at room temperature. The best treatment on day 30 was obtained in treatment C with 49.15% water content, 31.10% protein and organoleptic test value was 7.22 with the following criteria: clean appearance and compact; wadi distinctive aroma and taste interesting; savory flavor and preferred. Key words : Water content, wadi, Pangasius hypophthalmus, organoleptic test